2018
DOI: 10.1177/0954407018818693
|View full text |Cite
|
Sign up to set email alerts
|

An improved method of detecting engine misfire by sound quality metrics of radiated sound

Abstract: Existing engine misfire detection techniques require direct contact with hot vibrating engine component(s). Thus, they need costly sensors and regular maintenance. To overcome this limitation, a novel method is proposed to detect cylinder misfire using sound quality metrics of the radiated sound, measured either near the cylinder block or near the exhaust tailpipe. This method was tested on a four-stroke, four-cylinder spark-ignition engine over a wide range of load torques and speeds. Sound signals were measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…This experiment demonstrated that any of the methods mentioned may be efficiently applied to diagnose a misfire fault of an internal combustion engine. In another approach, Singh et al [11] used sound quality metrics (roughness, loudness, and fluctuation strength) into the SVM classifier to analyze and classify the engine block and tailpipe sounds. Using this technique, Sing and his co-workers reached an accuracy of 94% in the misfire diagnosis process.…”
Section: Introductionmentioning
confidence: 99%
“…This experiment demonstrated that any of the methods mentioned may be efficiently applied to diagnose a misfire fault of an internal combustion engine. In another approach, Singh et al [11] used sound quality metrics (roughness, loudness, and fluctuation strength) into the SVM classifier to analyze and classify the engine block and tailpipe sounds. Using this technique, Sing and his co-workers reached an accuracy of 94% in the misfire diagnosis process.…”
Section: Introductionmentioning
confidence: 99%
“…Misfires have been detected in a contact-less acoustic method with 94% accuracy, relative to 82% accuracy attained from vibration signals. Without opening the hood and recording at the exhaust, the authors reached 85% classification accuracy from audio (which again outperformed vibration) [39]. While some algorithms have been developed without physical process knowledge, others make use of system models to improve diagnostic performance.…”
Section: Engine and Transmissionmentioning
confidence: 98%
“…8,9 This property has made SVM as an effective supervised learning algorithm in recent years. 1012 For example, Jegadeeshwaran and Sugumaran 13 developed a fault diagnosis scheme for hydraulic brakes using SVM. It has been reported that SVM has advantages (in terms of good prediction accuracy, less model training time, and ability to handle unstructured and semi-structured data) in classification problems with small samples, high dimensions, and nonlinear data that make it widely popular for fault diagnosis and predictive health monitoring.…”
Section: Introductionmentioning
confidence: 99%